A fast particle filter pedestrian tracking method based on colour, texture and corresponding space information. (3rd September 2019) - Zhang, Yang; Yang, Shumin; Xin, Dongrong
In order to track pedestrians accurately, a fast particle filter pedestrian tracking method based on colour, texture and corresponding space information is proposed. In this algorithm, firstly, we extract space information of object pedestrian and disintegrate it into three local regions. In addition, employ the improved texture and colour information extract algorithm to get the joint texture and colour information from the corresponding sub-region. Finally, determine the position of object by colour-texture similarity indicator based on space division, and get the result of accurately track. In consideration of the multi thread information fusion algorithm need a larger number of particles, this factor could reduce the computational efficiency. Therefore, a wave integral histogram algorithm is proposed for improving arithmetic speed. The experiment carried out on videos, result indicates the effectiveness and efficiency of the proposed method, which can achieve higher accuracy than other tow state of the art algorithms in the actual traffic scene, and the real-time performance also has been improved considerably.